Utilitarian redundancy in local medical systems - theoretical and methodological contributions - Patrícia Muniz de Medeiros; Washington Soares Ferreira Júnior; Fabiane da Silva Queiroz (Journal of Ethnobiology and Ethnomedicine, 2020)
Abstract The utilitarian redundancy model (URM) is one of the recent contributions to ethnobiology. We argue that URM can be applied to access use-pressure on plant species, the resilience of socioecological systems (e.g., local medical systems), cultural keystone species, and the role of exotic species in social-ecological systems. Based on previous URM studies, we also emphasize the need to differ practical (considering plants and uses that are currently employed) and theoretical (considering both currently employed and potentially employed plants and uses) redundancy. Based on the main applications of the URM, we propose a new index to access redundancy of a therapeutic indication: the Uredit, so that Uredit = NSp + CR, were Uredit is the Utilitarian Redundancy Index for the therapeutic indication; NSp is the total number of species mentioned for the indication, and CR is the species’ contribution to redundancy (in terms of knowledge sharing). The maximum value that the Uredit could reach is twice the number of species employed for the therapeutic indication. We believe that this theoretical and methodological improvement in the model can improve comparisons of redundancy in different social-ecological systems. We also highlight some limitations of the URM (and our Uredit), and we believe that conscious reasons behind people’s decisions should be incorporated into future studies on the subject.